Does cultural distance matter in international stock market comovement? Evidence from emerging economies around the world - LUCEY, BRIAN MICHAEL (My University, 2010)
Prior research suggests an inverse relationship between geographic distance and financial market linkages. In this paper, we examine whether and how cultural distance between countries mitigates this finding. We find that country-pairs exhibit higher linkages if they have smaller cultural distance. The result remains significant to alternative measures of linkage. Finally, the cultural effect seems to be more pronounced for active trading country-pairs than thin-trading country-pairs.
PUBLISHED
Keywords: Emerging markets; International stock market comovement; Cultural distance